Student Expectations in a General Education Physics Course taught Using a Transformative-Learning Paradigm - Mistades, Voltaire (INTI International University, 2007)
A new general education curriculum has been implemented beginning of the academic year 2006-2007 for the freshman students of De La Salle University – Manila. The study documented how the cognitive expectations of non-science majors changed after taking up an Introductory Physics course that was taught using a transformative learning framework. The paper describes what cognitive expectations are, and provides readers with a preview of how the transformative learning paradigm was used in the Introductory Physics class. By comparing the cognitive expectations profile of the freshman during academic year 2005-2006 with the profile of the freshman of academic year 2006-2007, the data generated is a valuable input towards the implementation of the new general education curriculum.